Outcome of medulloblastoma in children treated with reduced-dose radiation therapy plus adjuvant chemotherapy - Nongnuch Sirachainan (2018)
Medulloblastoma is the most common malignant brain tumor in children. Post-surgical craniospinal irradiation (CSI; 30-36 Gy) plus local boost radiation therapy (RT; 54-56 Gy) is a standard treatment for children with medulloblastoma who are over 3 years old, resulting in a 5-year overall survival (OS) rate of 46% to 65% in average-risk patients and 50% in high-risk patients. The addition of chemotherapy has the benefit of reducing complications from radiation and improving the OS rate. Using this approach, the estimated 5-year OS rates for patients with average- and high-risk medulloblastomas treated with different protocols are 65% to 85% and 16% to 70%, respectively. In this study, we determined the outcome of patients with average- and high-risk medulloblastomas treated with reduced dosage CSI and chemotherapy with an oral etoposide-based regimen. The study included 49 patients, with a mean age of 7.7 ± 3.4 years. Twenty-six patients (53%) were classified as average-risk and 23 patients (47%) as high-risk. In the average-risk group, the 5-year progression free survival (PFS) rate was 62.9% ± 10% and the 5-year OS rate was 70.4% ± 9.5%. In the high-risk group the 5-year PFS rate was 48.9% ± 13% and the 5-year OS rate was 49.7% ± 13%. In the average-risk group, patients who received CSI of either 24 Gy (n = 20) or 36 Gy (n = 9) showed no difference in their 5-year PFS and OS rates. We found that patients who were ≤10 years old and patients who were female had a significantly better 5-year PFS rate. © 2010 Elsevier Ltd. All rights reserved.